RANCANG BANGUN APLIKASI MARKETPLACE PENATU MOBILE WEB BERBASIS RESPONSIVE WEB DAN FRAMEWORK EXPRESS.JS - Catherine Elfrida, Rossario; Farel Purba, Juan; Sudarma, Made; Shandyasa, I Wayan (Jurnal SPEKTRUM; Vol 11 No 3 (2024): Jurnal SPEKTRUM, 2024)
This research developed a mobile web marketplace application for laundry services to address user difficulties such as finding the nearest location, managing physical receipts, and obtaining service information. Utilizing a responsive web design approach and flexbox techniques, the front end of the application was designed to be optimal across various devices. The back end was built using Express.js with the controller-middleware-route concept to maintain code organization. Furthermore, the Geocoding API and Distance Matrix API were implemented to calculate the distance between customers and laundry services. Testing was conducted using black box testing by developers and usability testing by participants. The results indicated that the front end of the application provided an optimal user experience with an overall satisfaction rate of 89.57%, and the back end was effective in managing data with middleware features and the integration of the Geocoding API and Distance Matrix API, achieving a usability satisfaction rate of 89.22%. This research demonstrates that the responsive mobile web application is effective and efficient in assisting users in finding suitable laundry services, thereby enhancing convenience and service efficiency .